Cobalt‐promoted MoS2 nanosheets: A promising novel diesel hydrodesulfurization catalyst. Issue 3 (25th December 2019) - Abbasi, Ali; Karimi, Ali; Aghabozorg, Hamidreza; Sadighi, Sepehr; Aval, Maryam Alizadeh
Abstract: MoS2 has been commonly used as a catalyst in hydrodesulfurization (HDS) of petroleum cuts in crude oil refineries. In this study, the synthesis of unsupported MoS2 and Co‐promoted MoS2 nanosheets produced from molybdenum oxide and thiourea is reported. The synthesized samples were characterized by using x‐ray fluorescence, x‐ray diffraction, Brunauer–Emmett–Teller (BET), temperature‐programmed reduction, thermal gravimetric analysis, and transmission electron microscopy methods, and then they were utilized for HDS of diesel through a fixed‐bed catalytic reactor. Results indicated that a cobalt promoter affected both the number and the performance of active sites of the molybdenum sulfides, and the activity of the promoted MoS2 catalyst was consistently higher than that of the MoS2 catalyst. More significantly, the activity of the promoted catalyst was slightly declined during 48 h continuous HDS reaction, which indicated the stability of this catalyst. Additionally, during 12 h of test run, the HDS activity of the promoted catalyst was about 60% higher than MoS2 one.